A new host for Trypanosoma (Herpetosoma) renjifoi Deane, 1961, infecting Proechimys longicaudatus (Rodentia - Echimyidae) - Mello, Dalva A. (1978)
A Proechimys longicaudatus rodent was found naturally infected with Trypanosoma (Herpetosoma) renjifoi Deane in 1961. It was captured on the Água Limpa farm near Brasilia, the Federal District. This is the first account of this trypanosome in Central Brazil, and P. longicaudatus is a new host for this blood parasite.